Combinatorial ALD for the growth of ZnO/TiO2 nanolaminates and mixed ZnO/TiO2 nanostructured films. Issue 6 (24th February 2022) - Doyle, Shóna; Ryan, Louise; McCarthy, Melissa M.; Modreanu, Mircea; Schmidt, Michael; Laffir, Fathima; Povey, Ian M.; Pemble, Martyn E.
Abstract : The importance of understanding the growth fundamentals of ZnO/TiO2 nanolaminate structures deposited by atomic layer deposition is explored. Abstract : In this study, combinatorial atomic layer deposition (C-ALD) has been used to deposit layered ZnO and TiO2 nanolaminates on both oxide-covered Si(100) wafers and glass substrates to assess the influence of substrate and each layer on the structure of the resulting nanolaminates and their photoactivity towards dye degradation. In addition, for comparison to these layered structures, C-ALD has been used to directly create oxide films consisting of an approximately equal mixture of Zn 2+ and Ti 4+ ions using the concept of under-dosing in order to deposit sub-monolayer quantities of each oxide per complete C-ALD cycle. A nucleation delay was observed for ZnO deposited directly on the substrate and the subsequent TiO2 layer, the latter to a lesser extent. The reason for the difference in nucleation delay is due to the dissimilar surface groups. For the deliberately layered structures, it was found that ZnO appeared to possess a templating influence on the TiO2 layer grown subsequently on both substrate types. XRD analysis showed strong preferential orientation for (002) which indicates the polycrystalline manner of the ZnO film. XRD results also suggested that layer growth was substrate-dependent as crystalline TiO2 was only identified on glass substrates. The nanolaminate structures were found to be stable in that the layer structure remained intact after annealing at 400 °C for 1 hour in contrast to the comparison to the mixed ZnO : TiO2 (1 : 1) film which showed evidence of ZnO segregation and crystallisation. Concerning photocatalytic activity, no evidence was found for any enhancement of photoactivity in the mixed or nanolaminate films, the most photoactive films being those consisting of ZnO deposited onto glass substrates.